An orthogonal dual-regulation strategy for sensitive biosensing applications. Issue 9 (12th March 2022) - Yang, Xian; Wang, Jinhua; Gao, Zhongfeng; Zhang, Weiqi; Zhu, Hai; Song, Yongjun; Wang, Quan; Liu, Mingjie; Jiang, Lei; Huang, Yu; Xia, Fan
ABSTRACT: Biosensing systems based on controllable motion behaviors of droplets have attracted extensive attention, but still face challenges of insufficient sensitivity and uncontrollable dynamic range due to imprecise manipulation of droplet motion on the surfaces. Here, we report an orthogonal dual-regulation strategy for precise motion control of droplets and we demonstrate its utility as a sensitive sensing system with controllable dynamic ranges of sensing for adenosine triphosphate, miRNA, thrombin and kanamycin, as well as discrimination of five kinds of DNA. We endowed a DNA-contained bio-droplet sliding on a lubricant-infused structural surface with micro-grooves to separately adjust the resistance from liquid phase and solid phase. The resistance from liquid phase mainly depended on hydrophobic interaction between DNA and lubricant, which can be finely tuned by different DNA's average chain length. Meanwhile, the resistance from solid surface was determined by the energy barrier from the periodic micro-grooves, which can be adjusted by varying the droplet's sliding direction on the surface. The hydrophobic interaction is conformed to be orthogonal to the micro-grooves' anisotropic resistance by three different methods. This orthogonal dual-regulation strategy thus demonstrated its ability to precisely control bio-droplets' motion behaviors and sensitive detection with adjustable dynamic ranges for various bio-targets. The dual-regulation strategy will provide significant insights for super-wettable biosensors, visual inspection and beyond. Abstract : An orthogonal dual-regulation strategy was developed for droplets' precise motion control, and applied as a sensitive sensing system with controllable sensing dynamic ranges for various bio-markers.